Rediscovery of Begonia aliciae C.E.C. Fisch. (Begoniaceae) from the Western Ghats of Kerala - Kumar , E. S. Santhosh; Abdul Jabbar , M.; Saleem , M. (Rheedea, 2002)
Begonia aliciae C.E.C. Fisch., an endangered species of the Western Ghats, is rediscovered from its type locality after a lapse of 64 years of its first collection. A detailed description and illustrations are provided based on recent collection.